Production of actinorhodin by Streptomyces coelicolor in batch and fed-batch cultures - Ates, S; Elibol, E; Mavituna, F (Elsevier Sci Ltd, 1997)
Fed-batch fermentations of Streptomyces coelicolor in chemically defined medium in a 20 litre bioreactor were used to produce actinorhodin. Concentrated solutions of phosphate and nitrate with or without glucose were fed intermittently or continuously. Continuous feeding of glucose alone was found to be the best strategy for actinorhodin production. In this case, the specific productivity was almost twice that obtained in conventional batch fermentation. (C) 1997 Elsevier Science Ltd.
Keywords: Dispersed Growth; A3(2)